Problematyka kobieca w prasie lokalnej - Jurga-Wosik, Ewa (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The analysis of the content of local periodicals makes it possible to indicate two types of women’s issues. One presents both historical as well as modern images of women, while the other discusses women’s issues in relation to political, economic and social phenomena and events. The author of the paper attempts to answer the question of what women have found in- teresting and what they want to read about; whether we are dealing with sexism in the local press; whether publications on women’s issues are more frequently written by men or women; whether there is a set division of positions and competences available to women in the opera- tion of the local press and whether the fact that editors-in-chief are women influences the quality and quantity of women’s topics discussed. The conclusions corroborate the main hypothesis, namely that although there are certain exceptions, the local press largely reinforces a stereo- typical approach to women.
Women’s Issues in Local Press
Keywords: kobiety; prasa lokalna